2015
DOI: 10.1167/iovs.14-15540
|View full text |Cite
|
Sign up to set email alerts
|

Lamina Cribrosa Depth in Different Stages of Glaucoma

Abstract: In treated glaucoma, posterior LC displacement occurs mostly in the preperimetric and mild-to-moderate glaucoma stages. This warrants further investigation of LC depth as a parameter to monitor glaucoma progression in the early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 26 publications
6
74
0
1
Order By: Relevance
“…One investigation found deeper ALD with greater visual field loss in glaucoma patients, but no effect of age alone. 47,48 The baseline ALD is of less interest as a prognostic biomarker for glaucoma susceptibility than its dynamic mechanical properties. Human glaucoma eyes were stiffer by indirect clinical measures 49 and exhibit steeper stress-strain behavior in post mortem studies of the ONH 50 and sclera.…”
mentioning
confidence: 99%
“…One investigation found deeper ALD with greater visual field loss in glaucoma patients, but no effect of age alone. 47,48 The baseline ALD is of less interest as a prognostic biomarker for glaucoma susceptibility than its dynamic mechanical properties. Human glaucoma eyes were stiffer by indirect clinical measures 49 and exhibit steeper stress-strain behavior in post mortem studies of the ONH 50 and sclera.…”
mentioning
confidence: 99%
“…Seo et al [7] investigated the characteristics of the LC depth in healthy eyes using EDI SD-OCT and their average ALCS depth was similar to our result (402 ± 101.46 μm). Park et al [30] reported a mean ALCD of 344 μm in healthy controls. However, these patients were younger (mean age: 56 years) than our population and, according to Ren et al [3] that suggested a shallower anterior LC in older eyes than in younger eyes, this age gap may explain this difference.…”
Section: Discussionmentioning
confidence: 98%
“…Although the measurement of LC depth seems to be plainer than that of LC thickness, it too may be problematic. Most studies set the reference point for LC depth as Bruch's membrane opening (BMO) [11,26]. Since myopic optic discs have experienced peripapillary changes, including posterior bowing of the BMO, or peripapillary atrophy (PPA) in the absence of BM [27,28], LC depth may vary according to the position of the BMO or the presence of BM.…”
Section: Discussionmentioning
confidence: 99%